Evidence of stronger pitch angle scattering loss caused by oblique whistler‐mode waves as compared with quasi‐parallel waves. Issue 17 (2nd September 2014) - Li, W.; Mourenas, D.; Artemyev, A. V.; Agapitov, O. V.; Bortnik, J.; Albert, J. M.; Thorne, R. M.; Ni, B.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.
Abstract Wave normal distributions of lower‐band whistler‐mode waves observed outside the plasmapause exhibit two peaks: one near the parallel direction and the other at very oblique angles. We analyze a number of conjunction events between the Van Allen Probes near the equatorial plane and Polar Orbiting Environmental Satellites (POES) at conjugate low altitudes, where lower‐band whistler‐mode wave amplitudes were inferred from the two‐directional POES electron measurements over 30–100 keV, assuming that these waves were quasi‐parallel. For conjunction events, the wave amplitudes inferred from the POES electron measurements were found to be overestimated as compared with the Van Allen Probes measurements primarily for oblique waves and quasi‐parallel waves with small wave amplitudes (< ~20 pT) measured at low latitudes. This provides plausible experimental evidence of stronger pitch angle scattering loss caused by oblique waves than by quasi‐parallel waves with the same magnetic wave amplitudes, as predicted by numerical calculations.